Submucosal esophageal abscess evolved from a peritonsillar abscess diagnosed using esophagogastroduodenoscopy and endoscopic ultrasonography: A case report - Kazuhiro Yoshinaga; Tetsuo Watanabe; Kota Hiraoka; Takashi Hirano; Masashi Suzuki (Acta Oto-Laryngologica Case Reports)
An 83-year-old woman with suspected cervical abscess and laryngeal edema was transferred to our hospital for further examination and treatment. She was diagnosed with a left peritonsillar abscess and inflammatory spread to the esophagus and scheduled conservative treatment with antibiotics. Her clinical symptoms, including fever and, sore throat, and contrast computed tomography findings worsened four days after admission. She was diagnosed with esophageal submucosal abscess (ESA) based on esophagogastroduodenoscopy and endoscopic ultrasonography. Her abscess spontaneously drained, and blood tests showed improved inflammatory response, indicated by the white blood cell count and C-reactive protein concentration. Conservative treatment was continued, and the patient was discharged from the hospital without relapse. ESA needs to be differentiated from mediastinitis. Esophagogastroduodenoscopy and endoscopic ultrasonography are useful or diagnosing ESA.